Géographies sociales et appliquées, entre regards croisés et circulations universitaires : Wolfgang Hartke, les géographes français et les relations académiques franco-allemandes au XXe siècle - Nicolas Ginsburger (Cybergeo, 2015)
Wolfgang Hartke (1908-1997) is famous as one of the pioneers of the German social geography, but this essay deals with a more unnoticed aspect of his personal and professional life, his very close connections with his French colleagues between the 1920s and the end of the 20th century. In many ways, his research, his scientific friendships and collaborations, his academic and intellectual reputation and the reception of his ideas were characterized by a very special french-german relationship, in terms of intense human and conceptual networks and circulations. He was not the only German geographer working on and with France, specialy after 1945, but he was the first and the most active, his career long and even after his retirement. His unique position as a German adviser in the milieu of the French review L’Espace géographique was just the final form of this transnational work and presence, in contact with the more general context of a complex partnership between France and Germany.